The Role of Social Capital and Intellectual Capital Towards Increasing the Performance of Small and Medium Businesses: Peran Social Capital Dan Intellectual Capital Terhadap Peningkatan Kinerja Usaha Kecil Dan Menengah - Fitriyah, Hadiah; Setiyono, Wisnu Panggah; Rini, Dina Dwi Oktavia; Kurniati, Novita Yuli (Procedia of Social Sciences and Humanities, 2022)
The purpose of this study was to determine the role of Social Capital and Intellectual Capital on Improving the Performance of Small and Medium Enterprises. Organizational social capital has a big role in increasing business excellence. Therefore, social capital is the main capital that must be owned by an SME actor, thereby increasing his entrepreneurial spirit so that he can run his business. The sustainability of micro-businesses in batik is highly dependent on the ability to innovate. In this context, intellectual capital is the key to business success. Therefore, it is important to conduct a study on strategies to improve the performance of small and medium enterprises through the role of social capital and intellectual capital. The approach of this research is quantitative research. Data was collected by means of documentation through the distribution of questionnaires. The analytical method used in this research is SEM-PLS with the help of SmartPLS